1995
DOI: 10.1021/ma00118a026
|View full text |Cite
|
Sign up to set email alerts
|

Donor-Embedded Nonlinear Optical Side Chain Polyimides Containing No Flexible Tether: Materials of Exceptional Thermal Stability for Electrooptic Applications

Abstract: We describe here the preparation and characterization of the first processible nonlinear optical (NLO) polyimide where the chromophore is not incorporated using a flexible tether functionality. The polymer has a very high glass temperature and shows exceptional thermal and chemical stability. Poled samples also show outstanding orientational stability, consistent in part with the high glass transition temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 3 publications
(4 reference statements)
1
65
0
Order By: Relevance
“…Exceptionally high thermally stable polyimides were described by Verbiest 102,104) and Miller et al 103) The polymer Pe was shown to have a chemical stability up to temperatures of 350 8C for several hours, whereas the glass transition temperature was l350 8C. Pf on the other hand decomposes at a much lower temperature of 275 8 under the same experimental conditions.…”
Section: High Glass Transition Polymersmentioning
confidence: 83%
“…Exceptionally high thermally stable polyimides were described by Verbiest 102,104) and Miller et al 103) The polymer Pe was shown to have a chemical stability up to temperatures of 350 8C for several hours, whereas the glass transition temperature was l350 8C. Pf on the other hand decomposes at a much lower temperature of 275 8 under the same experimental conditions.…”
Section: High Glass Transition Polymersmentioning
confidence: 83%
“…These NLO polymers could be acquired by doping NLO chromophores into amorphous polymer matrices (guest-host systems) [3] or covalently incorporating NLO moiety onto polymer backbone. [4][5][6] NLO-phores with extended p-conjugated bridge functionalized with strong electron donors and acceptors can exhibit extremely large first hyperpolarizability, b. A variety of organic chromophores containing conjugated systems such as polyenes, [7,8] thiophene, [9 -12] stilbene, [13 -16] and azobenzene [4,17,18] compounds as well as terminal donor and acceptor groups, [19][20][21][22] have been investigated to exhibit large optical nonlinearity.…”
Section: Introductionmentioning
confidence: 99%
“…The NLO polyimides exhibiting high orientation stability were prepared by using diamines containing NLO chromophores 7,8 and through the introduction of chromophores to poly(hydroxyimide)s. 9 -12 The magnitude of the macroscopic nonlinear effect is determined by the number density of chromophores within the polymers. Thus, the former approach should be reliable for the introduction of chromophores in every repeating unit.…”
Section: Introductionmentioning
confidence: 99%